PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA QUESTION CARD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS IV SD NEGERI 066049 MEDAN HELVETIA - Friscilia Radika Br Siringo-Ringo; Antonius Remigius Abi; Patri Janson Silaban; Eka Kartika Silalahi; Anton Sitepu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a quantitative research method with an experimental research type. This research aims to determine the effect of the Problem Based Learning model assisted by Question Card media on students' critical thinking skills in the IPAS subject of grade IV at SD Negeri 066049 Medan Helvetia. The research subjects consisted of 34 fourth-grade students from the same school. The instruments used in this study were questionnaires and multiple-choice test items. The students' critical thinking skills showed an average pretest score of 57.06, and after the treatment using the Problem Based Learning model, the average posttest score increased to 82.35. The results indicate a strong influence of variable X on variable Y, with a correlation coefficient of 0.699. Given that the r_table value is 0.339, the alternative hypothesis (Ha) is accepted. Furthermore, hypothesis testing showed that the t_count was 24,070 while the t_table was 1.691, proving that the hypothesis is significant, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This demonstrates that the Problem Based Learning model assisted by Question Card media has a significant effect on students' critical thinking skills.